In situ modification of case-hardening steel 16MnCr5 by C and WC addition by means of powder bed fusion with laser beam of metals (PBF-LB/M) - Bartels, Dominic; Novotny, Tobias; Hentschel, Oliver; Huber, Florian; Mys, Ruslana; Merklein, Carsten; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2022)
Typical high-strength products are made from carbon-rich steels possessing relatively high carbon content, thus reducing weldability. In this work, preliminary studies on designing and tailoring a low-alloyed steel for the laser-based powder bed fusion (PBF-LB/M) process by adding carbon black (C) nanoparticles and tungsten carbide (WC) particles for enhancing the material properties are provided. First, the base material 16MnCr5 is modified with different concentrations of C and WC. It was found that an increased C and WC content resulted in an elevated material hardness in the as-built state. However, this comes at the cost of a poorer processability as pore formation increased for C-modified and crack tendency increased for WC-modified 16MnCr5. When applying a post-process quenching and optional tempering heat treatment, material hardness in the range of 615 HV can be achieved for C-enriched 16MnCr5 in the tempered state, which would be suitable for bearing and gearing applications. The addition of WC particles favored an improved wear resistance which is twice as high as the one of C-modified material for similar material hardness, showing the enormous potential of WC addition for reducing the wear rate. Complementary SEM and EDX analyses show that both the dilution and bonding zone of the WC particles are affected by the processing conditions and the WC concentration. Furthermore, it was found that a nearly defect-free fabrication of WC-enriched 16MnCr5 was possible for up to 2.5 wt.-% of WC, proving that the occurring defects are highly sensitive to the WC concentration.<br
Keywords: Additive manufacturing; PBF-LB/M; Selective laser melting; Case-hardening steel; In situ alloying; Hardness; Wear resistance; WC